Advanced glycation end products modulate electrophysiological remodeling of right ventricular outflow tract cardiomyocytes: A novel target for diabetes‐related ventricular arrhythmogenesis - Yao‐Chang Chen; Yen‐Yu Lu; Wen‐Shiann Wu; Yung‐Kuo Lin; Yi‐Ann Chen; Shih‐Ann Chen; Yi‐Jen Chen (Physiological Reports, 2022)
Abstract Diabetes mellitus is associated with cardiovascular disease and cardiac arrhythmia. Accumulation of advanced glycation end products closely correlates with cardiovascular complications through mitochondrial dysfunction or oxidative stress and evoke proliferative, inflammatory, and fibrotic reactions, which might impair cardiac electrophysiological characteristics and increase the incidence of cardiac arrhythmia. This study examined the mechanisms how advanced glycation end products may contribute to arrhythmogenesis of right ventricular outflow tract—a unique arrhythmogenic substrate. A whole‐cell patch clamp, conventional electrophysiological study, fluorescence imaging, Western blot, and confocal microscope were used to study the electrical activity, and Ca2+ homeostasis or signaling in isolated right ventricular outflow tract myocytes with and without advanced glycation end products (100 μg/ml). The advanced glycation end products treated right ventricular outflow tract myocytes had a similar action potential duration as the controls, but exhibited a lower L‐type Ca2+ current, higher late sodium current and transient outward current. Moreover, the advanced glycation end products treated right ventricular outflow tract myocytes had more intracellular Na+, reverse mode Na+–Ca2+ exchanger currents, intracellular and mitochondrial reactive oxygen species, and less intracellular Ca2+ transient and sarcoplasmic reticulum Ca2+ content with upregulated calcium homeostasis proteins and advanced glycation end products related signaling pathway proteins. In conclusions, advanced glycation end products modulate right ventricular outflow tract electrophysiological characteristics with larger late sodium current, intracellular Na+, reverse mode Na+–Ca2+ exchanger currents, and disturbed Ca2+ homeostasis through increased oxidative stress mediated by the activation of the advanced glycation end products signaling pathway.